Synthesis of 3-Aroyl-4-hydroxy-4-arylpiperidine Derivatives by DBU-Catalyzed Reactions of Amines with Vinyl Ketones - Liu, Xiaodong; Chen, Qiao; Li, Wenyi; Liang, Yuan; Wang, Rui (Synlett, 2012)
In one-pot cascade reaction, a series of functionalized 3-aroyl-4-hydroxy-4-arylpiperidine derivatives were prepared from sulfonamides and vinyl ketones with good to excellent yields and diastereoselectivities. The reaction was catalyzed by the commercially available Lewis base 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) and could be easily manipulated under mild condition.
Keywords: Michael addition; vinyl ketones; cascade reaction; cyclization; stereoselectivity